Transforming education: A review of the benefits of integrating mindfulness and meditation techniques in schools - Hilda Delavari; Mohammad Ebrahim Talebi; Haleh Delavari (English Education Journal, 2023)
This review article explores the growing interest in incorporating mindfulness and meditation practices into school settings, examines their potential benefits and effectiveness for students' well-being and academic performance. The article provides an overview of various mindfulness and meditation techniques, their theoretical underpinnings, and psychological mechanisms. With the method of literature review, four phases of designing, conducting, analysing, and structuring as well as writing the outcomes of review were held systematically. The present study found that discussion about the advantages of these practices were visible for students, including improved cognitive functioning, reduced stress and anxiety, enhanced emotional well-being, and better social skills and relationships. The review also addresses the implementation of mindfulness and meditation in schools that focuses on curriculum integration, teacher training, and challenges to implementation. Lastly, it highlights future research directions and recommendations to further understand and optimize these practices for students of different age groups and cultural contexts.